2014
DOI: 10.29074/ascls.27.4.209
|View full text |Cite
|
Sign up to set email alerts
|

From Technical Assistants to Critical Thinkers: From World War II to 2014

Abstract: A review of professional literature was conducted to examine the history of the education of medical laboratory practitioners. This comprehensive review included historical educational milestones from World War II to present day. During this time period the standard of two years of college required for matriculation into a medical technology program increased to four years. Critical thinking skills promoted in the educational model and applied in practice expanded from an analytic and psychomotor orientation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…None of the scienti c competencies reached consensus in this study which might be a bit surprising since there are publications discussing the future importance of critical and analytic thinking in the professions of laboratory medicine and management [29][30][31]. This might be explained by the fact that most of our panel members were Biomedical Laboratory Scientists working in routine hospital-based laboratories.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…None of the scienti c competencies reached consensus in this study which might be a bit surprising since there are publications discussing the future importance of critical and analytic thinking in the professions of laboratory medicine and management [29][30][31]. This might be explained by the fact that most of our panel members were Biomedical Laboratory Scientists working in routine hospital-based laboratories.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have shown that in the future, the functional speci cations for Biomedical Laboratory Scientist will evolve to include both deeper knowledge and new skills [29][30][31]. Deeper knowledge in new advanced laboratory methods and new skills connected to the growth of evidence-based laboratory medicine where there is a demand to choose the most convenient methods with respect to diagnostic, medical, ethical, economical, and societal aspects.…”
Section: Discussionmentioning
confidence: 99%